FuzzyInventory Model Under Two Storage Systemfor Deteriorating Items with Selling Price Dependent Demand and Shortages - et.al, Paramjit Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A fuzzy inventory model for a single deteriorating item, selling price dependent demand rate,constant deterioration rate and fully backlogged shortages has been developed. In the present market scenario,the management of inventory is of most important to reduce the total inventory cost.Uncertainty in the different prices and factors affecting inventory cost can’t dealt with crisp nature of components affecting inventory system. Therefore, to deal with uncertain situation of the market, a fuzzy based two warehouse system of inventory has been discussed in the present paper considering vague nature of holding cost, selling price and other components as well, in both ware-houses. The objective of this paper is to derive the optimal replenishment policy with defuzzification of fuzzy numbers using signed distance and centroid method to minimize the present worth of total relevant inventory cost per unit of time. First a crisp inventory model is developed and corresponding fuzzy inventory model has been derived considering triangular fuzzy numbers for components affecting inventory cost. With the help of numerical example effects of parameters are studied for both crisp a fuzzy models and sensitivity analysis is performed for selected parameters in both the cases.